1990
DOI: 10.1016/0735-1097(90)90326-k
|View full text |Cite
|
Sign up to set email alerts
|

The value of class IC antiarrhythmic drugs for acute conversion of paroxysmal atrial fibrillation or flutter to sinus rhythm

Abstract: In a single-blind randomized study, the efficacy and safety of intravenous propafenone (2 mg/kg body weight per 10 min) versus flecainide (2 mg/kg per 10 min) were assessed in 50 patients with atrial fibrillation or flutter. Treatment was considered successful if sinus rhythm occurred within 1 h. Conversion to sinus was achieved in 11 (55%) of 20 patients with atrial fibrillation treated with propafenone and in 18 (90%) of 20 with atrial fibrillation treated with flecainide (p less than 0.02). If atrial fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(83 citation statements)
references
References 30 publications
4
75
0
4
Order By: Relevance
“…Available data on the use of various regimens of propafenone loading in patients with organic heart disease are scant. This agent should be used cautiously or not at all for conversion of AF in such patients and should be avoided in patients with heart failure or severe obstructive lung disease (28,31,33,34,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data on the use of various regimens of propafenone loading in patients with organic heart disease are scant. This agent should be used cautiously or not at all for conversion of AF in such patients and should be avoided in patients with heart failure or severe obstructive lung disease (28,31,33,34,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Transient hypotension and mild neurological side effects may also occur. Overall, adverse reactions are slightly more frequent with flecainide than with propafenone and these drugs should be avoided in patients with underlying organic heart disease involving abnormal ventricular function (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In addition, the incidence of successful restoration and maintenance of sinus rhythm was higher in patients with recent-onset AF than in those with chronic AF. 7,8 These findings suggested that AF was a progressive disease and that AF might be selfperpetuating. Wijffels et al 9 demonstrated that maintenance of AF by pacing in the normal goat heart resulted in the development of sustained AF within 1 to 3 weeks; these findings suggested that shortening of the effective refractory period (ERP; the so-called "electrical remodeling") was the main underlying electrophysiological change.…”
mentioning
confidence: 92%
“…Persistent AF usually progresses to a permanent form and the successful restoration and maintenance of sinus rhythm largely depend on arrhythmia duration, with longstanding AF being more resistant to cardioversion and more prone to recurrence [6][7][8][9] . Both resistance to cardioversion and tendency of recurrence are strongly related to the development of electrophysiological substrates characterized by shortened atrial effective refractory period 2,4,5,[10][11][12][13] , slow conduction in the atrial myocardium 10,11,[14][15][16] and dispersion of refractoriness 4,13,17,18 .…”
Section: Introductionmentioning
confidence: 99%